Review Article: Advancing Cancer Treatment With Mesoporous Silica Nanoparticle-Based Theranostics - Wirawan, Delphine; Hulwana, Alfa Fildzah; Herdiana, Yedi (Universitas Padjadjaran (Unpad), 2023)
Cancer is a major cause of death globally. It is often detected at a late stage, whileconventional treatments are more effective during the early and middle stages.These traditional treatments also cause many side effects due to the lack oftargeted delivery. Nanotechnology, particularly mesoporous silica nanoparticles(MSNs), has been investigated for cancer treatment and diagnosis. Theranostics,which combine therapy and diagnostics, can provide simultaneous treatment anddetection, potentially lowering mortality rates. A literature review was conductedusing keywords such as mesoporous silica nanoparticles, cancer, diagnosis, andtherapy in online databases like PubMed. The results of this review were analyzedand compared with existing literature, aiming to provide a comprehensiveoverview of mesoporous silica nanoparticles as current cancer treatment anddiagnosis.Keywords: MSNs, cancer, theranostic, therapy, literature.